Jīvanmukti in transformation embodied liberation in Advaita and neo-Vedanta - Fort, Andrew O. (State Univ. of New York Press, 1998)
"Liberation (mukti) is a central concern in Hinduism, particularly in Advaita (nondual) Vedanta, perhaps the best known school of Hindu thought. There has been vigorous debate and analysis about the possibility and nature of liberation while living (jivanmukti) in Advaita from the time of Sankara, the school's founder, to the present day. While the general conclusion seems to be that one can achieve living liberation, members of the Advaita tradition also regularly express reservations about, or describe limitations to, full liberation while embodied." "Jivanmukti in Transformation examines the development and transformation of the concept of jivanmukti from the Upanisads to the modern era. It gives the most thorough treatment of the scholastic Advaita tradition on liberation while living, makes the novel argument for a distinct "Yogic Advaita" tradition found in the Yogavasistha and Jivanmuktiviveka, and explores the modern "neo-Vedanta" view of jivanmukti, which has been influenced by modern Western concepts like global ecumenism and humanistic social concern for all."--BOOK JACKET.